Knowledge, attitude and practice towards exercise among pregnant women - Zakaria, Nor Zuhailee (Universiti Sains Malaysia, 2015)
The main objective of this study is to determine the knowledge, attitude and practice toward exercise among pregnant women and to know the main barriers that prevent pregnant women from participated in exercise during pregnancy. Health Belief Model proposed was used to explain the phenomena by relating the theories with the current situations. Pregnant women were interviewed using semi-structured questions as it provides in-depth information. 14 pregnant women raging from aged between 20 - 40 years old were participated in this study. The present finding summarized that the main sources of information gather regarding the exercise during pregnancy included reading sources as internet and book, television and antenatal clinic. Pregnant women’s attitude towards exercise during pregnancy was favorable. Most of participants believed that exercises provided a lot of benefits. For example as makes delivery easier, reduce pain and muscle cramp, maintain body fitness and improve energy during and after pregnancy. However, there were some barriers that prevent pregnant women in this study from engaged in exercise. The main barriers included time constrain (doing housework, working and child care). Others barriers highlighted by participants were tired to exercise, afraid to exercise and had medical problem such as bleeding, cervix and cardiac disease. Findings from this study concluded that although knowledge was satisfactory and the women’s attitude was favorable, there are no pregnant women in this sample exercised during pregnancy, thus highlighting that exercise was inadequate among pregnant women in this study.